FORMATION OF LEATHER FILLED WITH MODIFIED SYNTAN AND TANIDE COMPOSITION - DANYLKOVYCH АNATOLII; LISHCHUK, VIKTOR; SANGINOVA, OLGA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The technology of manufacturing leather material for the upper of shoes from semi-finished chrome tanning obtained from raw cow hides been has been developed. The technology at the filling-plasticization stage involves the use of a syntane-tanide composition modified with alkylcarboxyethanolamine of aliphatic acids of fraction C7–9. The filling and plasticizing composition includes syntanе BNS TU 17-06-165-89 and mimosa extract tanids with a content of the main substance of 81.7%. The semi-finished product is plasticized with Fosfol L-1301 emulsion of Cromogenia Units, S.A., Spain. Chemical reagents in the structure of the material are fixed by potassium alum modified with sodium formate. All previous and subsequent processes and operations are performed according to the industrial technology of the enterprise "Chinbar". The resulting semi-finished product is characterized by a volumetric yield of 256 cm3/100 g of protein, a specific surface area of 71 m2/g, which are 8.0 and 11.0% higher than the industrial sample. Deformation properties of topographic areas and coefficients of uniformity of topographic areas of leather materials at loads of 10.0 MPa and rupture were calculated. At the same time, a more effective characteristic of the homogeneity of the material structure is the uniformity factor at a load of 10.0 MPa. The leather material obtained by the experimental technology has a uniformly oriented structure with an arithmetic average coefficient of uniformity of 1.0, and the industrial material has a transversely oriented structure with an arithmetic average coefficient of uniformity of 0.83. The advantage of the experimental material over the industrial one in terms of the complex of physico-chemical and technological properties and the coefficient of uniformity increases the efficiency of its use for the manufacture of leather products. The obtained leather material meets the requirements of DSTU 2726-94 "Leathers for shoe uppers. Specifications".